MDA5 attenuate autophagy in chicken embryo fibroblasts infected with IBDV. Issue 2 (4th March 2022) - Yu, M.; Li, R.; Wan, M.; Chen, J.; Shen, X.; Li, G.; Ge, M.; Zhang, R.
ABSTRACT: 1. The role of melanoma differentiation-associated protein 5 (MDA5) in infectious bursal disease virus (IBDV)-induced autophagy was studied in chicken embryos. 2. Chicken embryo fibroblasts (CEF) were used as the research model and small interfering RNA (siRNA), western blot, indirect enzyme-linked immunosorbent assay (ELISA), real-time fluorescence quantitative polymerase chain reaction (PCR) and transmission electron microscopy were used to detect autophagy, IBDV replication, CEF damage, and activation of both MDA5 and its signalling pathway. 3. The results showed that CEF infected with IBDV activated the intracellular MDA5 signalling pathway and caused autophagy via inactivation of the AKT/mTOR pathway. While autophagy promotes IBDV proliferation, MDA5 weakens IBDV-induced CEF autophagy thus inhibiting IBDV replication and protecting CEF cells. 4. The results indicated that chMDA5 can be activated by IBDV and attenuate CEF autophagy caused by IBDV infection, thereby inhibiting IBDV replication. This study provided a foundation for further exploring the relationship between viruses, autophagy and the pathogenic mechanism of the MDA5 pathway involved in IBDV.